Strategi Pengembangan Ekowisata Mangrove Cuku Nyinyi Desa Sidodadi Kecamatan Teluk Pandan Kabupaten Pesawaran dengan Menggunakan Pendekatan Analisis SWOT - Rizky Augia; Fadhil Arief Dharmawan (Yayasan Literasi Sains Indonesia, 2025)
The Cuku Nyinyi Mangrove Ecotourism in Sidodadi Village, Teluk Pandan District, Pesawaran Regency, has great potential as a conservation-based tourism destination that supports environmental preservation and community welfare. However, its development still faces several challenges, such as limited supporting facilities, inadequate transportation access, and suboptimal marketing efforts. This study employs a descriptive qualitative method with SWOT analysis, based on participatory observation and Focus Group Discussion (FGD) with six respondents. The analysis results indicate that this ecotourism site falls into cell V in the I-E Matrix (Medium-Moderate), suggesting that the appropriate strategy is to hold and maintain, focusing on optimizing digital promotion, improving tourism facilities, and fostering partnerships with various stakeholders. The SWOT Quadrant Analysis also places this ecotourism site in Quadrant I (Strengths-Opportunities), indicating that internal strengths can be leveraged to capitalize on existing external opportunities. Key recommended strategies include developing conservation-based educational tourism programs, innovating mangrove-based tourism products, improving infrastructure, and utilizing digital marketing to enhance visibility and attractiveness. The findings highlight those strategies based on promotion, tourism product innovation, and infrastructure improvement have significant potential to boost the competitiveness of this ecotourism site. Therefore, synergy among local governments, ecotourism managers, and other stakeholders is essential to ensure sustainability and effectiveness of its development.